2004
DOI: 10.1111/j.1460-2695.2004.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cycle fatigue of 1Cr–18Ni–9Ti stainless steel and related weld metal under axial, torsional and 90° out‐of‐phase loading

Abstract: A B S T R A C TThe fatigue behaviour of base metal and weld joints of 1Cr-18Ni-9Ti stainless steel has been studied under uniaxial, torsional and 90 • out-of-phase loading. A significant degree of additional hardening is found for both base metal and weld metal under 90 • out-of-phase loading. Both base metal and weld metal have the same cyclic stable stressstrain relationship under torsional cyclic loading and 90 • out-of-phase cyclic loading. Base metal exhibits higher cyclic stress than weld metal under uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…A rotating aero engine receives cyclic loading under thermal and mechanical stresses which cause multiaxial low cycle fatigue (LCF). Under non-proportional loading in which the principal directions of stress and strain are changed cyclically, previous studies have reported a drastic reduction in the failure life with an accompanying additional cyclic hardening [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] depending on both the loading path and the material [6,8,10,13,16]. In addition, some studies about the fatigue property of Ti alloys have been reported [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…A rotating aero engine receives cyclic loading under thermal and mechanical stresses which cause multiaxial low cycle fatigue (LCF). Under non-proportional loading in which the principal directions of stress and strain are changed cyclically, previous studies have reported a drastic reduction in the failure life with an accompanying additional cyclic hardening [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] depending on both the loading path and the material [6,8,10,13,16]. In addition, some studies about the fatigue property of Ti alloys have been reported [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…While Fatemi and Socie (FS) [16] built their work on this model but proposed that the normal strain term should be replaced by normal stress so as to account for the effect of mean stress. This approach has been proven effective for a variety of materials [29][30][31][32]. For materials showing normal fracture, Smith et al (SWT) [18] suggested that the maximum normal strain plane should be considered as the critical plane.…”
Section: Introductionmentioning
confidence: 99%
“…The welding wire of MG70S-6 with a diameter of 2 mm is used. The manufacture of the welded metal specimen is followed by [23,24]. A well-designed notch is first machined at the center of the base metal bar, and the notch is then filled with weld metal.…”
Section: Specimens and Loading Pathmentioning
confidence: 99%